Long-Term Patient-Reported Outcomes After Surgery for Superior Canal Dehiscence Syndrome. Issue 9 (October 2017) - Alkhafaji, Mohammed S.; Varma, Sanskriti; Pross, Seth E.; Sharon, Jeffrey D.; Nellis, Jason C.; Santina, Charles C. Della; Minor, Lloyd B.; Carey, John P.
Abstract : Objective: Evaluate the long-term patient-reported outcomes of surgery for superior canal dehiscence syndrome (SCDS). Study Design: Cross-sectional survey. Setting: Tertiary referral center. Patients: Adults who have undergone surgery for SCDS with at least 1 year since surgery. Main Outcome Measure(s): Primary outcome: change in symptoms that led to surgery. Secondary outcomes: change in 11 SCDS-associated symptoms, change in psychosocial metrics, and willingness to recommend surgery to friends with SCDS. Results: Ninety-three (43%) respondents completed the survey with mean (SD) time since surgery of 5.3 (3.6) years. Ninety-five percent of respondents reported the symptoms that led them to have surgery were "somewhat better, " "much better, " or "completely cured." Those with unilateral symptoms were more likely to report improvement than those with bilateral symptoms. There was no difference between those with short (1–5 yr) versus long (5–20 yr) follow-up. Each of the SCDS-associated symptoms showed significant improvement. The largest improvements were for autophony, pulsatile tinnitus, audible bodily sounds, and sensitivity to loud sound. Headaches, imbalance, dizziness, and brain fog showed the least improvements. Most patients reported improvements in quality of life, mood, and ability to function at work and socially. Ninety-five percent of patients would recommend SCDS surgery. Conclusions: Respondents demonstrated durable improvements in the symptoms that led them to have surgery. Auditory symptoms had the greatest improvements. Headaches, imbalance, dizziness, and brain fog showed the least improvements. Nearly, all patients would recommend SCDS surgery to others. These results can be used to counsel patients regarding the lasting benefits of surgery for SCDS.